Understanding Economics in the Context of Prosperity Concept - Demiessie, Habtamu Girma (Research in Business and Management, 2022)
Conventional understanding on the purpose of the economy and/or the essence of economic science is dealing with the decision making behavior of economic agents in a way for optimal allocation of scarce resources in production, consumption and exchange of economic goods & services activities. And, the four economic resources are land, labor, capital and entrepreneurship. On the other hand, the term economy, in its conception with prosperity, is quite different. For one, in the context of prosperity, there are seven (7) types of economic resources. These are: Money, Food, Clothing, Recreation, Rest, Time and Energy. Moreover, the focus of economy in prosperity is not limited to material satisfaction, but also spiritual acquisition. Therefore, the economics of prosperity entails maximizing wellness of people (communities) through optimal allocation on those mentioned seven (7) dimensions of resources, which can be categorized as material and non-material by their virtues. More importantly, the essence of economics in the context of prosperity is setting standards and/or principles on how people can manage a balanced life, where their material and spiritual needs are better served. This paper tries to characterize ideals of prosperity concept with fundamentals of economic science.